Sebastian Wojciechowski, Przemysław Osiewicz, Zrozumieć współczesny terroryzm. Wybrane aspekty fenomenu, Difin, Warszawa 2017, ss. 251 + 1 nlb. - Kraj, Kazimierz (Przegląd Strategiczny, 2017)
abstrakt